2009
DOI: 10.1159/000239236
|View full text |Cite
|
Sign up to set email alerts
|

Time between Symptom Onset and Assessment in Age-Related Macular Degeneration with Subfoveal Choroidal Neovascularization

Abstract: Background: Therapy delay in neovascular age-related macular degeneration (NV-AMD) is associated with risk of visual deterioration. Methods: Retrospective cross section analysis including patients with NV-AMD who received fluorescein angiography (FA). The time elapsed from symptom onset to assessment was analysed in relation to different factors. Inclusion criteria were: age >50 years, symptom onset within 6 months before assessment, no previous AMD therapy, indication for vascular endothelial growth factor in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 55 publications
1
7
0
Order By: Relevance
“…2011). There are several reasons for this, amongst which a worse visual acuity and higher age at baseline as well as a considerable delay to treatment in routine clinical settings seem to be the most important (Schalnus et al. 2010; Mariani et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2011). There are several reasons for this, amongst which a worse visual acuity and higher age at baseline as well as a considerable delay to treatment in routine clinical settings seem to be the most important (Schalnus et al. 2010; Mariani et al.…”
Section: Discussionmentioning
confidence: 99%
“…Clinician-determined retreatment after an upload phase appears to be less effective in improving BCVA compared with randomized controlled trials (Kumar et al 2011). There are several reasons for this, amongst which a worse visual acuity and higher age at baseline as well as a considerable delay to treatment in routine clinical settings seem to be the most important (Schalnus et al 2010; Mariani et al 2011). Available evidence points towards baseline BCVA predicting treatment outcomes with poor baseline visual acuity determining poor treatment outcomes (Shona et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Deferral of therapy after onset of CNV has a negative effect on visual acuity outcome [1214] because untreated CNV continues to grow at a mean growth rate of 10–18 μm per day [15,16]. One study showed that a delay in treatment of more than 28 days compared with 28 days or less resulted in a statistically significant greater percent of patients with at least 1 line loss of vision (p = 0.01) [17].…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, a number of attempts have been made to document this period retrospectively. 11,12 Retrospective evaluation can be difficult, however, since the onset of symptoms often cannot readily be determined without detailed specific questioning of the patient by a trained clinician. Additionally, the timing of symptom awareness is likely to differ, depending on the visual acuity in the other eye.…”
mentioning
confidence: 99%